Kemampuan pemecahan masalah dalam menyelesaikan soal materi pecahan oleh siswa SMP ditinjau dari tahapan Polya - Januar Rahmasari Saputri; Helti Lygia Mampouw (Math Didactic: Jurnal Pendidikan Matematika, 2018)
This study aims to describe the problem solving ability in solving the matter of fractional by junior high school students by Polya’s step. The type of this research is descriptive research with qualitative approach. The subjects of the study consisted of 3 students of grade VII SMP namely 1 high-ability students, 1 medium-ability student, and 1 low-ability students. The results showed that: (1) High ability student were able to solving mathematical problem of fractional material by going through all stages of Polya. (2) Medium ability students to solving mathematical problems of fractional materials have not been able to go through all stages of Polya. They are only able to go through the stage of understanding the problem. (3) Low ability student to solving mathematical problems of fractional materials have not been able to go through all stages of Polya. They are only able to go through the stage of understanding the problem and making plans.